Da não mensuração à mensuração da natureza no ocidente no início da modernidade - Bergamo, Maurício Sérgio (2016)
This dissertation aims to analyze the relationship between the epistemological processes and the vision of nature established by man in modernity. This task refers to a scientific, philosophical and artistic itinerary closely linked to the progress of the western civilization. We will highlight the main characteristics of Ancient and Medieval knowledge and thus we will defend that invisible, intangible and sacred faces, qualitative attributes of the nature of these times, result from the development of metaphysical and allegorical sets developed by thinkers who lived and dedicated themselves, intellectually, to these historical periodization. Similarly, we will defend that the quantitative, measurable and mechanical image of the cosmos began to be developed to the extent that the artisans and the Renaissance engineers began to offer pragmatic possibilities to science. The adoption of mathematical principles allied to experimentation of natural phenomena, in the epistemological processes conducted by natural philosophers, scientists, and philosophers, is also presented as one of the main elements contributing to the homogeneous objective and unified representation of the cosmos. Hesiod, Plato, Aristotle, St. Augustine, St. Thomas Aquinas, Leonardo da Vinci, Copernicus, Giordano Bruno, Johannes Kepler, Galileo Galileo, Isaac Newton, Descartes and Francis Bacon will be some of the characters investigated in this dissertation. Through this historical and epistemological journey, we will conduct a deep analysis of some of the major historical events and the methods used by these big names. Hence, we want to defend that quantitative representation, homogeneous and objective in nature, is derived (in part) of the attitudes and behavior adopted by intellectuals in their scientific research. Therefore, we want to emphasize that the purpose of the phenomena and the ontological laws of nature came to be linked to men's intentions. With the unveiling of the secrets of nature promoted by the Mathematics and Experimentation, men duped with the mysteries of the soul, forward transcend inventions and mechanical ingenuity. And nature, in turn, lost its qualitative attributes to become a mechanic and measurable body.